His rebel bride eaudiobook - Black, Shayla (Brothers in Arms, 2017)
A reckless warrior, Kieran Broderick was half-Irish, yet bound to fight for the English crown. So when King Henry decreed that he take an Irish wife to quell rebellion there, he had little choice. Newly dubbed the earl of Kildare, Kieran travels to Langmore Castle, seat of the lawless O'Shea family, to choose a bride. When he picks Maeve, a fetching lass who seems sweetly submissive, he soon learns she's a fiery, clever woman. When she refuses to allow him into her bed or her heart, he finds himself fighting the most daunting battle of his life. But Kieran will never give up. He's determined to conquer his rebellious beauty—body and soul. Contains mature themes.